Duchessina : a novel of Catherine de Medici - Meyer, Carolyn, 1935- (Meyer, Carolyn, 1935- Young royals., 2007)
While her tyrannical family is out of favor in Italy, young Catherine de Medici is raised in convents, then in 1533, when she is fourteen, her uncle, Pope Clement VII, arranges for her marriage to prince Henri of France, who is destined to become king.